Intelligent photovoltaic system to maximize the capture of solar energy - Christian Ovalle Paulino; Luis Rojas Nieves; Hugo Villaverde Medrano; Ernesto Paiva Peredo (Institute of Advanced Engineering and Science, 2023)
The large consumption of electricity worldwide has an impact on the environment which can be said to alter climate change, the degradation of the ozone layer and acid rain. A house has an average daily consumption of 270kWh, this is why solar panels are very useful and can help to have a renewable energy at low costs. To create an intelligent photovoltaic system, different electronic sensors can be applied to follow the sunlight through a series of instructions in some programming software. The article proposes to prototype an intelligent photovoltaic system, based on artificial intelligence with a neural network library